2015
DOI: 10.1597/14-274r1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cleft Lip Measurements and Maxillary Growth in Patients With Unilateral Cleft Lip and Palate

Abstract: Objective :  Maxillary growth in patients with cleft lip and palate is highly variable. The authors' aim was to investigate associations between preoperative cleft lip measurements and maxillary growth determined cephalometrically in patients with complete unilateral cleft lip and palate (cUCLP). Design :  Retrospective cross-sectional study. Patients :  Children with cUCLP. Methods :  Preoperative cleft lip measurements were made at the time of primary cheiloplasty and available for each patient. Maxillary gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 33 publications
(59 reference statements)
1
16
0
1
Order By: Relevance
“…Children born with cleft lip and/or palate are more likely to experience a range of dental anomalies and skeletal issues when compared with non-cleft counterparts (Antonarakis et al, 2016; Lai et al, 2008). Therefore, they often require complex long-term orthodontic treatment, often in combination with maxillofacial surgery, in order to produce a good facial appearance, with an aesthetic, functional and stable occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children born with cleft lip and/or palate are more likely to experience a range of dental anomalies and skeletal issues when compared with non-cleft counterparts (Antonarakis et al, 2016; Lai et al, 2008). Therefore, they often require complex long-term orthodontic treatment, often in combination with maxillofacial surgery, in order to produce a good facial appearance, with an aesthetic, functional and stable occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…This condition may lead to a variety of dental issues, with studies showing that 94% of cleft patients are found to have at least one dental anomaly (Nicholls, 2016). In addition, the form and shape of the maxillary arch may also be affected: vertical, antero-posterior and transverse growth is often reduced with potential subsequent adverse alteration of the dental archform (Antonarakis et al, 2016). The resulting effects on the dental occlusion of these patients can make them more challenging to manage orthodontically.…”
Section: Introductionmentioning
confidence: 99%
“…While such a measure of lip deficiency may not intuitively make sense when evaluating nose deformity, deficiencies of the lateral lip have been associated with hypoplasia. Measured deficiencies of lateral lip have been associated with dental agenesis 23,24 , dental arch deficiencies 25 , and maxillary hypoplasia 24 . The lateral lip ratio may therefore be a surrogate objective measure of cleft related hypoplasia when assessing cleft severity and the associated nasal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, investigating the association between cleft size at birth and cephalometric measurements before orthodontics showed a significantly negative correlation between dimensions of the defect and maxillary length and protrusion (Liao et al, 2010; Chiu et al, 2011; Antonarakis et al, 2016). Patients with large clefts and small arch circumference or arch length have been shown to have a less favorable maxillary protrusion at age of 5 years (Peltomaki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%